MEMAHAMI KEPEMIMPINAN TRANSFORMASIONAL DALAM PERSPEKTIF MANAJEMEN PERUBAHAN - Hermastho, Bima (JURNAL BISNIS STRATEGI, 2001)
The importance of leadership to change management process is underscored by the fact that change, by definition, requires creating a new system and then institutionalizing the new approaches. While change management depends on leadership to be enacted, to date there has been little integration of these two bodies of literature. Thus the purpose of this articles is to draw parallels between the change literature and the leadership literature : specifically, the transformational leadership literature that is primarely concerned with the capabilities required to enact change succesfully.